Women leaders in the workplace: perceptions of career barriers, facilitators and change. Issue 2 (2nd April 2020) - Coleman, Marianne
Abstract : Questions of gender equality pervade our culture, particularly in the world of work, where about three quarters of leaders are men. This paper draws on 60 interviews with women in the UK, in senior leadership roles, in a variety of fields. The research questions address the interviewees' perceptions of three areas: career challenges (or barriers) for women who wish to access leadership roles; the main facilitators of career progress for women and changes they have seen and anticipate seeing for women leaders at work. The main challenges or barriers were perceived as a masculine work culture; discrimination and the glass ceiling; gendered stereotyping; and the difficulties of combining work and family life. Facilitators were their own determination and agency, mentoring and networking, with little mention of support through places of work. With regard to change for women at work, they saw the glass ceiling as moving gradually upwards, although some more 'masculine' industries were more difficult for women to navigate. With the exception of the women in higher education, they did not support feminism or an affirmative stance towards women's progress and in the private sector were accepting of the prioritisation of business motives over equity issues.